Application of spectrophotometric fingerprint in cluster analysis for starch origin determination - Sakač, Nikola (Array, 2020)
The botanical origin of starch is of importance in industrial applications and food pro-cessing because it may influence the properties of the final product. Current microscopic methods are time-consuming. Starch consists of an origin-dependent amylose/amylopec-tin ratio. Triiodide ions bind characteristically to the amylose and amylopectin depending on the botanical origin of the starch. The absorbance of the starch-triiodide complex was measured for wheat, potato, corn, rye, barley, rice, tapioca and unknown origin starch, and within the different cultivars. Each starch sample had specific parameters: starch-triio-dide complex peak wavelength maximum (λmax/nm), maximum absorbance change at λmax (ΔA) and λmax shift towards the unknown origin starch sample values. The visible ab-sorption spectra (500-800 nm) for each starch sample were used as a unique fingerprint, and then elaborated by cluster analysis. The cluster analysis managed to distinguish data of two clusters, a cereal type cluster and a potato/tapioca/rice starch cluster. The cereal subclusters extensively distinguished wheat/barley/rye starches from corn starches. Data for cultivars were mostly in good agreement within the same subclaster. The proposed method that combines cluster analysis and visible absorbance data for starch-triiodide complex was able to distinguish starch of different botanical origins and cultivars within the same species. This method is simpler and more convenient than standard time-con-suming methods.